KOMPARASI PERH ITUNGAN DRAFT SURVEY ANTARA METODE KONVENSIONAL DENGAN METODE MICROSOFT EXCEL DALAM MENGHITUNG BERAT MUATAN PADA KAPAL - Fajar Tyas Adi; Priyo Suhadi (JURNAL JALASENA, 2020)
The calculatton of the draft survey is a highly anticipated result as a reference of business transacttons and as a reference to the determination of tax payments to the state. Fast in terms of time and precise calculation accuracy becomes a demand in business services especially in international business. Given the delay impacted the loss of a fine to be paid by the recipient of goods for being late in the process of loading or known as Demurraage. The problem raised in this research is how to apply the calculation of the optimal draft survey with the speed of time and accuracy of calculation. The research method used in this research is quantitative analysis by calculate of cargolood/ verify the calculation of the number of vessels betweet the conventional draft survey method and the method of draft survey microsoft excel which refers to the data of the ship that has been verified by the PT. Surveyor Indonesia. The results obtained from this research is the calculation by the method of draft survey microsoft excel has a high level of accuracy because the chances of error due to human error is smaller that the calculation by manual. It consume also more effective time compared to manual methods (more time efficient).